Developing New Indonesia Circular Economy Indicators: A Lesson Learnt from European Union - Siti Afiani Musyarofah; Alva Edy Tontowi; Nur Aini Masruroh; Budhi Sholeh Wibowo; IDAA Warmadewanthi; Arman Hakim Nasution; Mohamad Khoiru Rusydi; Gogor Arif Handiwibowo; Gita Widi Bhawika (Institut Teknologi Sepuluh Nopember, 2023)
Circular Economy (CE) right now has been a point of interest among countries in the world as a commitment of the Paris Agreement to solve global environmental problems, which are simultaneously beneficial to economics. However, presently there is no single indicator available that easily be used as a CE standard due to various stresses among the countries. There are different approaches among countries in developing CE indicators, although they are still within the scope of the environmental and economic aspects. CE indicators could be developed based on region covering several countries, government/country level, and company level. Those indicators refer to the region and government policy and market or users of the product and a society where its public area would receive waste that the company might produce. This review will discuss only European Union and Poland, representing regions and countries. A region like the European Union (EU) considers ten indicators for CE, consisting of 21 sub-indicators. These indicators include self-sufficiency in raw materials, procurement for the green public, waste generation, food waste, recycling rate, recovery of specific waste streams, recycled materials to raw materials demand contribution, raw material trade-in, investment, jobs, and gross value-added, patents of secondary and recycling raw materials. While Poland, as a member of the EU, developed 25 CE indicators based on the seven dimensions of the economic point of view, such as economic prosperity, zero waste, innovative, renewable energy- based economy, low carbon, smart economy, and spatially effective economy. Implementing a Comparative Analysis Method that compares one indicator to another, the results show that 6 of 10 indicators belonging to the EU overlap with four indicators of 25 belonging to Poland. Covering all indicators of both regions and countries, thus it would become 29 selected indicators that might be useful for developing Indonesia CE- Indicators, which are presently unavailable yet.